Vocal state change through laryngeal development - Yisi S. Zhang (Nature Portfolio, 2019)
Vocal development in humans and primate model systems is typically attributed to changing neural circuits. Here the authors show in marmoset monkeys that biomechanical changes in the vocal organ underlie the transition from infant cries to adult contact calls, demonstrating that vocal development is not solely due to neural control.